EFEKTIVITAS PEMBELAJARAN TEMATIK DI MADRASAH IBTIDAIYAH MUHAMMADIYAH 3 AL FURQAN BANJARMASIN - Nurlaila Dwe Khairiyati; Siti Noor Halisa; Zahran; Ahmad Ridho; Aslamiah; Diani Ayu Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Thematic learning is an integrated learning method that combines various disciplines into one learning theme to provide students with a beneficial learning experience. This research aims to analyze the effectiveness of thematic learning at MIS Muhammadiyah 3 Al-Furqan Banjarmasin. Data was collected through interviews and questionnaires with teachers using qualitative methods with a case study approach. The research results show that teachers face problems in terms of limited time, resources, and ability to use technology. However, thematic learning is considered effective for improving students understanding and critical thinking skills. It is highly recommended to provide ongoing training to educators and provide more complete resources to help implement thematic learning.